Living the Qur’an: Exploring Dalā’il Al-Khairāt in Indonesia as a Bridge Between Devotional Tradition and Emotional Experience - Muhammad Yusuf Pratama; M. Sihabudin; Mokh. Sya’roni; Saepudin (Millati: Journal of Islamic Studies and Humanities, 2025)
This research addresses the surprising phenomenon that Dalā’il al-Khairāt—a tradition of reciting ṣalawat in Indonesia—is not only a worship ritual but also a significant psychological and social coping mechanism. However, integrating Living Qur’an studies with emotional well-being analysis is rarely explored. The research aims to fill this gap by examining the role of this tradition in building individual and community emotional resilience. The research was conducted in a Javanese pesantren and an Acehnese community using qualitative (in-depth interviews, observations) and quantitative (emotional satisfaction survey) mixed methods. Results showed that 70% of participants experienced increased calmness, optimism, and inner peace, with a strong correlation between the duration of practice and emotional stability (100% of Santri practicing for more than 1 year reported positive impacts). This study contributes to the development of Living Qur’an by linking sacred texts, ritual practices, and mental health. It provides interdisciplinary empirical evidence on the role of spirituality in stress management and social cohesion, particularly in Indonesia’s multicultural society.